PENGARUH CITRA PERUSAHAAN TERHADAP MINAT KONSUMEN (Evaluasi Penjualan Jasa Kamar Aston Karimun City hotel - Sella Kurnia Sari; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The research was conducted in Aston Karimun City Hotel. The setting of the problem is how the influence of corporate image on consumer interest in the hotel. The purpose of this study was to determine the influence of corporate image on consumer interest Aston Karimun City Hotel. The author uses descriptive quantitative analysis methods, and some theories about the company's image and interests. Indicators used in the independent variable is the personality, reputation, values, corporate identity and the dependent variable is the interest. Collecting data using questionnaires and interviews. The sample used was accidental sampling. Source of data used are primary data or data obtained directly from the questionnaires and interviews. Secondary data is data obtained from company documents Aston Karimun city hotel. These results indicate that the influence of corporate image variables against consumer interest. And the existence of a strong relationship between the variables of interest corporate image to the consumer. Keywords: corporate image, interest, hotel.